2013
DOI: 10.1007/s10461-013-0661-3
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Cell Phone Support for Non-adherent HIV-Infected Youth and Young Adults: An Initial Randomized and Controlled Intervention Trial

Abstract: This randomized behavioral trial examined whether youth living with HIV (YLH) receiving cell-phone support with study funded phone plans, demonstrated improved adherence and viral control during the 24 week intervention and 24 weeks post-intervention compared to controls. Monday through Friday phone calls confirmed medications were taken, provided problem-solving support, and referred to services to address adherence barriers. Of 37 participants (ages 15–24), 62 % were male and 70 % were African American. Self… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
171
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 99 publications
(175 citation statements)
references
References 20 publications
4
171
0
Order By: Relevance
“…14 The study was conducted between February 2010 and November 2011. Briefly, 37 participants were enrolled with 19 randomized to the intervention and 18 to the control group.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…14 The study was conducted between February 2010 and November 2011. Briefly, 37 participants were enrolled with 19 randomized to the intervention and 18 to the control group.…”
Section: Methodsmentioning
confidence: 99%
“…Adherence decreased in the control group over the 48 weeks. 14 Findings indicate a very nonadherent cohort that likely represent the least adherent youth living with HIV.…”
Section: Introductionmentioning
confidence: 97%
“…7 A systematic review (2009) of 14 RCTs using text message interventions showed positive preventative health and clinical care behavioral outcomes. 8 Moreover, access to technology does not appear to be a limiting factor in the implementation of such a program: in a focus group of urban minority and low-income youth, participants denied the existence of a Bdigital divide^or that a technology-based intervention would fail due to access difficulties.…”
Section: Introductionmentioning
confidence: 99%
“…While texting has a strong evidence base for adults [14] [16] [37], use with youth, while intuitively appealing given the widespread use of texting, remains supported largely only by pilot studies. [19] Similarly, phone-based problem solving discussion with adherence coaches has preliminary evidence [20] demonstrated in a pilot study. Our work leverages the wealth of pilot evidence to create an intervention approach with demonstrated promise but not yet rigorously evaluated.…”
Section: Discussionmentioning
confidence: 98%
“…Evidence has supported the utility of phone-based outreach using a problem solving approach. [20] [21] In a recent review, harnessing mobile phone technology was identified as a promising area for future interventions encouraging optimal adherence among YLWH. [18] Furthermore, evidence suggests using phone-based technology to engage adolescent social support networks may promote optimal engagement in care and adherence to medications.…”
Section: Outreach Between Clinic Visitsmentioning
confidence: 99%